Foreign Investors and the Colombian Peace Process (2016)
The International Investment Regime (iir) materialises in international arbitral tribunals that protect the rights of foreign investors. Could these tribunals hamper the implementation of exceptional measures agreed to end armed conflicts? The principle of proportionality, usually employed to balance competing demands such as the interests of international investors and the right of states to self-determination, could fall short when it comes to the concept of a nation and a society's right to peace. Focusing on the Colombian peace process, this article argues that the agreement on land redistribution, a cornerstone of the peace agreements, benefits the whole society, including foreign investors. However, the colonialist nature of the iir could lead foreign investors, who see their investments and expected profits affected, to demand compensation for governmental land acquisition. The Colombian case suggests powerful lessons for the willingness of transitional states to defend their people's right to peace in international tribunals. © 2016 Koninklijke Brill NV, Leiden, The Netherlands.